PENGARUH PELATIHAN DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA BADAN KEUANGAN DAN ASET DAERAH KABUPATEN SUMEDANG - Nining Kurniasih; Aa Kartiwa (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2021)
Human Resources (HR) is the most expensive asset of an organization compared to other assets because HR is the main driver of the company's organization. Human Resources also always have to improve their competence, along with the development of the era of globalization. In order to compete with other human resources, it is required to obtain, develop, and maintain quality Human Resources. The purpose of the study was to determine the effect of training on employee performance, to determine the effect of competence on employee performance, and to determine the effect of training and competence on employee performance. Data Collection Methods Data collection in this study was carried out in the following ways: Questionnaires used with a Likert scale. The results obtained that training has a positive influence on employee performance. The significance value of t is less than 5% (0.000), indicating that training (X1) has a positive and significant effect on employee performance (Y). Thus, it can be concluded that Ho is rejected and H1 is accepted, so the hypothesis which states that training has a positive influence on employee performance can be accepted. Competence has a positive influence on employee performance. From the calculation results, it is obtained that the t-count value for the competency variable. The significance value of t is less than 5% (0.000), indicating that competence (X2) has a positive and significant influence on employee performance (Y). Thus it can be concluded that Ho is rejected and H2 is accepted, so the hypothesis that competence has a positive influence on employee performance can be accepted